The steering system case study: power assisted steering system / Abdul Hapiz Hj Mohd Taib … [et al.] - Mohd Taib, Abdul Hapiz; Jamaluddin, Mohd Azwan Affendi; Abd Majid, Mohd Faizal; Bohari, Mohd Firdaos (Faculty of Mechanical Engineering, 2001)
Steering system is one of the most important systems that a vehicle should have and consider. It is not only important but also a necessity to every vehicle in today’s challenging world. With the new and improved networks of road, the need for compatible steering system is ever increasing day by day. This is what we’re trying to exaggerate from this project. Mostly, this project is about the available steering systems in the automotives industry nowadays. We will try to bring out the systems and types of steering system that usually taken for granted by some individuals who will only think of steering system usability aspect and not from what this system can contribute to their driving experience. As our special study case, we chose the power assisted steering system or commonly known as “power steering" system. This system incorporates the principles of hydraulics to help absorb some of steering effort applied by the driver to maneuver their vehicles. Besides the advantages of this system that will be discussed later on, there are also some disadvantages that can be associated to this system. This will also be discussed later on as we go along. There will be some explanation regarding other steering system such as the “rack-and-pinion”, "recirculating-bail, and some of the latest innovations regarding steering systems in the automotives world. All this can be found under the sub topic “ Future of Power Steering”